PESTA ADAT SEBAGAI SARANA PEMBELAJARAN NILAI BUDAYA DALAM PENDIDIKAN MASYARAKAT DI DESA ALOR KECIL KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Nurlaila B Arsyad; Tabita Plaikari, Halena Muna Bekata, Umiyani Kona, Trivonia Atta, Tabita A Serangkai, Tersia Lengmal (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to present the traditional feast as a means of learning cultural values in community education in alor kecil village, alor barat laut district, alor district, research data analysis using qualitative descriptive analysis. The data used in the research is qualitative data. Field observation and interview data collection techniques, interviews with Mr Karim Antoni, this traditional party also functions as a medium to strengthen social relations between citizens and provide education to the younger generation about the importance of maintaining local traditions and culture. Activities in the traditional feast, such as traditional rituals, traditional dances, and customary deliberations, become a learning platform that involves all members of the community.Based on the research results, it can be concluded that the traditional feast in Alor Kecil Village is not only part of the tradition, but also functions as a means of cultural education. This traditional feast is effective in instilling cultural values to the community, especially the younger generation, while maintaining the sustainability of local traditions and cultural identity.